Insights into the Evolutionary Relationships of LytA Autolysin and Ply Pneumolysin-Like Genes in Streptococcus pneumoniae and Related Streptococci - Morales, María (Genome Biol Evol, 2015)
Streptococcus pneumoniae (pneumococcus) is a major human pathogen. The main pneumococcal autolysin LytA and the pneumolysin Ply are two of the bacterium’s most important virulence factors. The lytA- and ply-related genes are also found in other streptococci of the Mitis group (SMG). The precise characteristics of the lytA-related—but not the ply-related—genes of SMG and their prophages have been previously described. A search of the more than 400 SMG genomic sequences available in public databases (ca. 300 for S. pneumoniae), showed Streptococcus pseudopneumoniae IS7493 to harbor four ply-related genes, two of which (plyA and plyB) have 98% identical nucleotides. The plyA homolog of S. pseudopneumoniae is conserved in all S. pneumoniae strains, and seems to be included in a pathogenicity island together with the lytA gene. However, only nonencapsulated S. pneumoniae strains possess a plyB gene, which is part of an integrative and conjugative element. Notably, the existence of a bacterial lytA-related gene in a genome is linked to the presence of plyA and vice versa. The present analysis also shows there are eight main types of plyA−lytA genomic islands. A possible stepwise scenario for the evolution of the plyA−lytA island in S. pneumoniae is proposed.